Dynamic Functional Connectivity Reveals Abnormal Variability in the Amygdala Subregions of Children With Attention-Deficit/Hyperactivity Disorder - Yang, Yue; Yang, Binrang; Zhang, Linlin; Peng, Gang; Fang, Diangang (Frontiers in Neuroscience, 2021)
Objective: This research aims to determine whether dynamic functional connectivity (dFC) based on amygdala subregions was altered in children with attention deficit hyperactivity disorder (ADHD). Methods: The dFC based on amygdala subregions was systematically calculated via a sliding time window method among 75 children with ADHD and 20 healthy control (HC) children. Results: Compared with the HC group, the right basolateral amygdala (BLA) signified higher dFC with the left superior frontal gyrus, and the right superficial amygdala (SFA) exhibited significantly higher dFC with the right prefrontal cortex in the ADHD group. The dFC based on the subregions of the amygdala (right centromedial amygdala, bilateral BLA, and SFA) highlighted a positive association with anxiety symptoms in the ADHD group. Conclusion: Functional connectivity based on the amygdala is more unstable in children with ADHD. By demonstrating an association between the stability of functional connectivity based on the amygdala and anxiety, this study may contribute to providing a new direction for investigating the internal mechanism of ADHD.